MOTIF RITUAL PEZIARAH MAKAM SUNAN GUNUNG JATI CIREBON - Wiwik Novianti (Jurnal Ilmu Komunikasi Acta Diurna, 2017)
The tomb of Sunan Gunung Jati is a tomb that is considered sacred not only by the Javanese butalso by the Chinese. As the tomb of one of the scholars of Islamic propagation on the island of Java,this tomb is crowded with pilgrims. This study uses phenomenology research strategy to explainthe understanding, experience and meaning of pilgrims of the tomb of Sunan Gunung Jatiagainst the rituals performed in the tomb. This study is based on interviews of pilgrims who comein the tomb complex of Sunan Gunung Jati, Cirebon. The results showed there are four motivespilgrims perform rituals, namely economic motives, social motives, cultural motives, and spiritualmotives.